Emprendimiento social y empresas sociales en la ciudad de Loja, aplicación del método Delphi para determinar el perfil del emprendedor social y los emprendimientos sociales año 2014 - Palacio Jaramillo, Geovanny Víctor (2015)
The purpose of this research is to analyze social entrepreneurship and social enterprises in the city of Loja and determine the profile of the entrepreneur. In the city of Loja 13 organizations of social enterprises supported by government and private organizations were identified. From the research collected using the Delphi method with 2 rounds of surveys at 25 experts from Loja city has concluded that social enterprises are supported by the government, the university and the community, managed by leaders, entrepreneurship most recognized is the Mission Smile Foundation. It was identified that there are barriers to create social enterprises and entrepreneurship run as such, lack of capital, the very tight credit policies, lack of information and lack of concern for fostering productive sector. It is recommended that the Government together with supporting agencies engaged in training and advising leaders and communities involved, supporting and financing depending on the projects presented.